PROJECT-BASED LEARNING AS A SIGNIFICANT APPROACH TO BUILD XXI CENTURY SKILLS - Rozikova, Rano (Журнал иностранных языков и лингвистики, 2021)
Project-based learning as a learner-centred and innovative approach to learning has endless real-world applications that avail a variety of strategies that are essential for lasting success of learners in the 21st century. Students benefit from this method driving their own learning through communication, collaboration, problem solving and critical thinking. This article provides basic insights into the importance of this contemporary approach highlighting the contribution of it in developing 21st century skills.